1984
DOI: 10.1111/j.1600-0528.1984.tb01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian longitudinal study of time and order of eruption of primary teeth

Abstract: Timing and sequence of eruption of primary teeth were studied longitudinally in 164 healthy Australian children. Eruption of primary teeth typically began between 7 and 8 months and was completed by 28 months. Tooth eruption was not significantly related to growth rate or to psychomotor maturity. Comparison of the eruption ages in this study with those from longitudinal studies in other countries suggests that no real changes in these have occurred over 40 yr despite increased affluence in industrialised count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
17

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 6 publications
5
26
0
17
Order By: Relevance
“…Further, our findings of earlier eruption of second molars in the mandible and the tendency of canines and first molars to be chronologically advanced in the maxilla is in agreement with many authors (3,4,12). Indian children experienced delayed eruption of primary teeth when compared to their counterparts in other populations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Further, our findings of earlier eruption of second molars in the mandible and the tendency of canines and first molars to be chronologically advanced in the maxilla is in agreement with many authors (3,4,12). Indian children experienced delayed eruption of primary teeth when compared to their counterparts in other populations.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, dental formulas are used to estimate biological age and to track children's growth (10). Longitudinal studies provide information on the ages of eruption of individual teeth, along with their variations (4,5,11,12) unclear in the literature (11). Oziegbe et al (16) suggested genetic and molecular studies to confirm the possible association of earlier emergence times of primary teeth to accelerated growth in boys during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the results presented here suggest that this also applies to modern human deciduous teeth. First, clinical longitudinal studies of living children (Lysell et al, 1962;Roche et al, 1964;Hitchcock et al, 1984;Holman and Yamaguchi, 2005;Folayan et al, 2007;Woodroffe et al, 2010) report the mean deciduous eruption (emergence through the gingiva) sequence for mandibular and maxillary teeth: di1, di2, dm1, dc1, and dm2. This eruption sequence is the same as the mandibular enamel initiation sequence reported here (Fig.…”
Section: Retzius Line Periodicitymentioning
confidence: 99%
“…Mean emergence times in our twin cohort were two months later, on average, than those reported by Hitchcock et al (1984) for healthy Australian singletons, but the order of mean emergence times for the different teeth was as expected.…”
Section: Discussionmentioning
confidence: 55%